Systemic Inflammation Evaluated by Interleukin-6 or C-Reactive Protein in Critically Ill Patients: Results From the FROG-ICU Study - Picod, Adrien; Morisson, Louis; de Roquetaillade, Charles; Sadoune, Malha; Mebazaa, Alexandre; Gayat, Etienne; Davison, Beth A.; Cotter, Gad; Chousterman, Benjamin Glenn (Frontiers in Immunology, 2022)
Abstract Background: The prognostic impact of high concentration of interleukin-6 (IL-6) or C-reactive protein (CRP), two routinely available markers of systemic inflammation in the general population of critically ill patients remain unclear. In a large cohort of critically ill patients including septic and non-septic patients, we assessed the relationship between baseline IL-6 or CRP and mortality, organ dysfunction and the need for organ support. This was an ancillary analysis of the prospective French and euRopean Outcome reGistry in Intensive Care Units study (FROG-ICU) including patients with a requirement for invasive mechanical ventilation and/or vasoactive drug support for more than 24 hours following intensive care unit (ICU) admission. The primary objective was to determine the association between baseline IL-6 or CRP concentration and survival until day-90. Secondary outcomes included organ dysfunction as evaluated by the Sequential Organ Failure Assessment (SOFA) score, and the need for organ support, including vasopressors/inotropes and/or renal replacement therapy (RRT). Results: Median IL-6 and CRP concentrations (n = 2,076) at baseline were 100.9 pg/mL (IQR 43.5-261.7) and 143.7 mg/L (IQR 78.6-219.8), respectively. Day-90 mortality was 30%. High IL-6 or CRP were associated with worse 90-day survival (Hazard ratios 1.92 [1.63-2.26] and 1.21 [1.03-1.41], respectively after adjustment on SAPS-II. High IL-6 was also associated with the need of organ-support therapies, such as vasopressors/inotropes (OR 2.67 [2.15-3.31]) and RRT (OR 1.55 [1.26-1.91]), including when considering only patients independent from those supports at the time of IL-6 measurement. Associations between high CRP and organ support were inconsistent. Conclusion: IL-6 appears to be preferred over CRP to appreciate critically ill patients’ prognosis.